Description Of Giving Blood Supplement Tablets To Donor Haemoglobin Levels in PMI Banyumas Regency - Febriana, Gita Dwi; Setyaji, Yoki (Academic Hospital Journal, 2025)
Background: Based on data from the Banyumas Regency PMI for August 2023, it is stated that there are 182 requests for blood products every day, but can only fulfil the demand for blood products at 152 blood bags/day, which means that in one day, the Banyumas Regency PMI still lacks 30 blood bags of blood. Everyday. Therefore, this is the background for UDD PMI Kab. Banyumas to provide additional blood supplements of Fe 60 mg and Folic Acid 0.4 mg to donors who failed due to low haemoglobin levels, namely < 12.5 gr/dL. Giving blood supplement tablets is considered to be able to increase haemoglobin levels more quickly than other vitamin supplements because they contain Fe or iron. The purpose of this study was to determine the increase in haemoglobin levels before and after giving blood supplements to blood donors in UDD PMI Banyumas.Method: This quantitative research uses an analytical observational method (Cross-Sectional Study), with a Purposive sampling technique using the Slovin Formula, resulting in 24 samples. Of the 24 prospective blood donors who failed the HB screening selection, they were given treatment with blood supplements of 5 tablets, which were consumed once a day.Result:  The average result of checking the haemoglobin level before administering the blood supplement was 11.48 gr/dL. After taking the blood supplement, the donor checked the haemoglobin level again, and the average haemoglobin level was 12.57 gr/dL. Based on the results of pre- and post-blood supplement examinations, the results showed an average increase in haemoglobin levels of 1.09 gr/dL.Conclusion: Prospective blood donors who consumed blood supplement tablets, namely Fe 12.45 mg and Folic Acid 0.5 mg, 1 tablet per day for 5 days, experienced an average increase in haemoglobin levels of 1.09 gr/dL.